Lost Symbols in the Historic City of Puebla in Mexico - Hernández Sánchez, Adriana; De La Torre Sánchez, Christian Enrique (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2022)
Since its origin, the city of Puebla has had representative elements in its public spaces that have survived for a long time, they are ornamental and utilitarian objects which are landmarks of the city. Street furniture is a benchmark of identity too. All elements have legends, they are references that have given identity to streets and avenues. Natural elements also refer to a city’s identity, like trees. But the natural element that defined origin, trace and growth of the city is one of the least visible. In the sixties, the San Francisco River was piped, as a sign of the new modernity, and today it is a boulevard where thousands of cars pass. Thus, bridges and other types of elements that the population still remember, mainly the elderly, have been forgotten. In recent years, some initiatives have emerged to rescue the historical memory of daily life and the revaluation of representative objects of the city center, such as the Casa Analco Community Museum project, coordinated by the Faculty of Architecture of BUAP in collaboration with residents of the Analco neighborhood. This article discusses both the monuments, their relics, elements of nature that shape the city's identity, as well as the gradual loss of these symbols.